Perancangan Data Warehouse Pada Software Laboratorium PT. Sainfest - Listyowati Purwopeni Sulis (LPPM Universitas Sains dan Teknologi Komputer, 2023)
This research is to analyze the existing database at the software laboratory center to obtain the necessary information and design a data warehouse to integrate existing data and provide global information. The method used is the method of analysis and planning. The method of analysis is carried out through reviewing and carrying out system analysis, carrying out analysis and identification of system vulnerabilities, and analyzing problem solving. And the data warehouse design method is implemented by applying the nine steps (Nine-Step Methodology) used by Ralph Kimball to design the star model. The result is a data warehouse that provides some global information that is global, meaningful, integrated and can be viewed from different perspectives and is useful for managers in decision making. A separate repository of functioning databases. A software lab center is already needed to help managers make strategic decisions quickly and accurately.